Synthesis and Spectral Studies of Cu(II) Coordination Compounds of 4[N-(cinnamalidene)amino] Antipyrine Semicarbazone - Singh, Lakshman; Kumar Sharma, Deepak; Singh, Upma; Kumar, Alok (Asian Journal of Chemistry, 2016)
A series of five coordination compounds of copper(II) with 4[N-(cinnamalidene)amino] antipyrine semicarbazone (CAPS) has been described in this work. Characterization of these coordination compounds were made on the basis of elemental analysis, molecular weight, magnetic moment, conductivity measurements, infrared and electronic spectra. In all the coordination compounds CAPS behaves as tridentate (N,N,O) ligand. Thermal properties of these compounds were also investigated.